The association between circadian rhythm of cortisol and shift work regularity among midwives-A multicenter study in Southeast China - Xin-xin Huang; Xiu-min Jiang; Qing-Xiang Zheng; Xiao-Qian Chen (Frontiers Media S.A., 2022)
ObjectiveThis article aims to explore the association between the trends of cortisol rhythm and the regularity of shift work among midwives.MethodsMidwives from six Southeast Chinese hospitals were recruited through cluster sampling in a multi-center cross-sectional study. Urine samples were collected half an hour after waking up, at 11:00, 19:00, and 23:00 on two consecutive days in a longitudinal cohort. The urinary cortisol was assayed by the chemiluminescence method.ResultsA total of 86 midwives were included in this study, contributing 688 cortisol samples. The midwives displayed a circadian rhythm in cortisol secretion, with zeniths in the morning and nadirs in the evening. The trend of the first day was repeated on the second day. Although the total working hours per week of the two groups, namely the regular shift group (N = 43) and the irregular shift group (N = 43), were the same, significant main effects of groups (F = 62.569, p < 0.001), time (F = 45.304, p < 0.001), and group-by-time interaction (F = 226.695, p < 0.001) were indicated through linear mixed models. The main effect of day was not statistically significant, with F = 0.105 and p = 0.746. The fluctuation range of cortisol curve in the group with irregular schedules was slightly lower than that in the group with regular schedules.ConclusionOur results may indicate that cortisol was more inhibited in midwives with irregular shift patterns than those with regular shift patterns. It is necessary to further study the relationship between cortisol rhythm and patterns of midwives' shifts in future so as to lay a foundation for hospital managers to develop a more reasonable scheduling system for midwives with the further purpose to minimize their occupational fatigue and ensure the safety of mothers and infants.